(3JWHjbGJ aj GdJaGYdjI (B-(3GdLRGFQ GfehPLG(B-s - (3SejI (B, (3HhQbYIs ((3bSfWjfI (B:s (3CdaG ddhKGFb(B,s, 2019)
(3JWQb gPG GdcJGH Gdi ehVhY GdUMGaI GdQbejI , hef CLd OQGSI gPG GdehVhY abO GTJedJ gPg GdOQGSI Ydi YOI aUhd JfGhdJ HGdHMK GdeJZjQGJ GdCSGSjI GdeJYdbI HGdehVhY, dJJhRY HPdc gPg GdaUhd cGdBJj(B: (3GdaUd GdChd hgh GdGWGQ GdefgLj ddOQGSI, NUU dWQM GdGTcGdjI hJSGDdGJ GdHMK, CgOGa GdOQGSI hcPG YQV COhGJ JMdjd GdHjGfGJ hcPG GdJOGHjQ GdEeHQjbjI ddOQGSI, HGdEVGaI Edi GdfehPL GdEQTGOj GdhXjaj fXQjI GdCLfOI Ch JQJjH GdChdhjI hfXQjI OhQI GdGgJeGe HGdbVGjG h eONd fTQ GdeHJcQGJ (B. (3GdaUd GdKGfj(B: (3JVef eMJhi GdeGOI GdEYdGejI GdJaGYdjI aj GdUMa GdQbejI GdLRGFQjI (B((3GdTQhb Chf dGjf ` GdNHQ Chf dGjf ` GdfgGQ Chf dGjf(B) - (3Gdafhf GdUMajI ddehGO GdGYdGejI GdJaGYdjI aj GdUMa GdQbejI GdLRGFQjI , hGdJaGYdjI YHQ GdbQGAGJ hGdJYGdjb hehGbY GdJhGUd GdGaJQGVj ddehGO GdGYdGejI GdSGHbI GdPcQ(B. (3, GVGaI Gdi GdJWHjbGJ GdJaGYdjI aj gPg GdCNjQI aGdfJGFL GdYGeI ddOQGSI GdJMdjdjI hcPG YQVgG , h CNjQG fJGFL GdOQGSI GdMGdjI HfJGFL GdOQGSGJ GdSGHbI hcPG fJGFL GdOQGSI aj VhA GdaQVjGJ haj GdCNjQ BaGb GdOQGSI hNGJeJgG(B.s
(3GdHHdjhZQGajG (B((3U(B.247- 156)s
Keywords: (3GdJaGYdjIs; (3GdUMGaI GdQbejIs